Development of an Operating Theatre Management Model in the Situation of the COVID-19 Epidemic in Rajavithi Hospital - Yutthanartjinda, Ladda; Sornchai, Anong; Kaewmak, Jinjutha (Nursing Journal of The Ministry of Public Health, 2023)
This research and development study aimed to develop an operating theatre management model in the situation of the COVID-19 epidemic in Rajavithi Hospital, and to examine its effectiveness. The study was conducted in 4 phases: 1) study the situation of operating room management in the situation of the COVID-19 pandemic, 2) development of an operating room management model in the epidemic situation of COVID-19, 3) examine the effectiveness of the developed model, and 4) certify the operating room management model. The sample consisted of 60 patients undergoing surgery at Rajavithi Hospital, divided into 30 participants in the control group and 30 participants in the experimental group, and 210 operating room personnel who worked with COVID-19 patients. These included 105 nurses and 105 multi-professionals in the operating theatre. The research instruments included an experimental instrument, which was the developed model, and instruments developed by researchers and validated by three experts to collect data on both patients and personal outcomes. Quantitative data were analyzed using percentage, mean and standard deviation and qualitative data were analyzed using content analysis. The results showed that the operating theatre management model consisted of 3 components, including structure, staff and system. The developed model was found to be effective. Using the operating theatre management model, there was no incident of surgery on the wrong-person, wrong-site, wrong-procedure, and wrong-patient. There were no reports of infected nurses from practice and the waiting time for surgery was statistically significantly reduced (p=.011), and patients were highly satisfied with the model (Mean=4.69, SD=.38). Scrub and circulating nurses perceived their self-efficacy at a high level (Mean=4.50, SD=.44) and coordinator nurses perceived their self-efficacy at the highest level (Mean=4.59, SD=.45).